Trend And Development Of Semisolid Metal Joining Processing - Salleh, Mohd Shukor; Mohammed, M.N.; Omar, Mohd Zaidi; Sajuri, Zainuddin; Alhawari, Khaled Salem (Hindawi Publishing Corporation, 2015)

(untitled)
The semisolid metal joining (SSMJ) process or thixojoining process has recently been developed based on the principles of SSM processing,which is a technology that involves the formation of metal alloys between solidus and liquidus temperatures.Thixojoining has many potential benefits,which has encouraged researchers to carry out feasibility studies on various materials that could be utilized in this process and which could transform the production of metal components.This paper reviews the findings in the literature to date in this evolving field,specifically,the experimental details, technology considerations for industrialization,and advantages and disadvantages of the various types of SSMJ methods that have been proposed.It also presents details of the range of materials that have been joined by using the SSMJ process.Furthermore,it highlights the huge potential of this process and future directions for further research.